Detection of glucose-derived d- and l-lactate in cancer cells by the use of a chiral NMR shift reagent - Eul Hyun Suh (BMC, 2021)
Abstract Background Excessive lactate production, a hallmark of cancer, is largely formed by the reduction of pyruvate via lactate dehydrogenase (LDH) to l-lactate. Although d-lactate can also be produced from glucose via the methylglyoxal pathway in small amounts, less is known about the amount of d-lactate produced in cancer cells. Since the stereoisomers of lactate cannot be distinguished by conventional 1H NMR spectroscopy, a chiral NMR shift reagent was used to fully resolve the 1H NMR resonances of d- and l-lactate. Methods The production of l-lactate from glucose and d-lactate from methylglyoxal was first demonstrated in freshly isolated red blood cells using the chiral NMR shift reagent, YbDO3A-trisamide. Then, two different cell lines with high GLO1 expression (H1648 and H 1395) were selected from a panel of over 80 well-characterized human NSCLC cell lines, grown to confluence in standard tissue culture media, washed with phosphate-buffered saline, and exposed to glucose in a buffer for 4 h. After 4 h, a small volume of extracellular fluid was collected and mixed with YbDO3A-trisamide for analysis by 1H NMR spectroscopy. Results A suspension of freshly isolated red blood cells exposed to 5mM glucose produced l-lactate as expected but very little d-lactate. To evaluate the utility of the chiral NMR shift reagent, methylglyoxal was then added to red cells along with glucose to stimulate the production of d-lactate via the glyoxalate pathway. In this case, both d-lactate and l-lactate were produced and their NMR chemical shifts assigned. NSCLC cell lines with different expression levels of GLO1 produced both l- and d-lactate after incubation with glucose and glutamine alone. A GLO1-deleted parental cell line (3553T3) showed no production of d-lactate from glucose while re-expression of GLO1 resulted in higher production of d-lactate. Conclusions The shift-reagent-aided NMR technique demonstrates that d-lactate is produced from glucose in NSCLC cells via the methylglyoxal pathway. The biological role of d-lactate is uncertain but a convenient method for monitoring d-lactate production could provide new insights into the biological roles of d- versus l-lactate in cancer metabolism.